Data mining for business analytics : concepts, techniques and applications in Python /: concepts, techniques and applications in Python. (2019) - Shmueli, Galit, 1971-; Bruce, Peter C, 1953-; Gedeck, Peter; Patel, Nitin R (Nitin Ratilal)
No abstract available